Genetic and molecular analysis of the X chromosomal region 14B17-14C4 in Drosophila melanogaster: loss of function in NONA, a nuclear protein common to many cell types, results in specific physiological and behavioral defects. - Stanewsky, R.; Rendahl, K.G.; Dill, M.; Saumweber, H. (Genetics, 1993)
We have performed a genetic analysis of the 14C region of the X chromosome of Drosophila melanogaster to isolate loss of function alleles of no-on-transient A (nonA; 14C1-2; 1-52.3). NONA is a nuclear protein common to many cell types, which is present in many puffs on polytene chromosomes. Sequence data suggest that the protein contains a pair of RNA binding motifs (RRM) found in many single-strand nucleic acid binding proteins. Hypomorphic alleles of this gene, which lead to aberrant visual and courtship song behavior, still contain normally distributed nonA RNA and NONA protein in embryos, and in all available alleles NONA protein is present in puffs of third instar larval polytene chromosomes. We find that complete loss of this general nuclear protein is semilethal in hemizygous males and homozygous cell lethal in the female germline. Surviving males show more extreme defects in nervous system function than have been described for the hypomorphic alleles. Five other essential genes that reside within this region have been partially characterized.